Perancangan Sistem Detektor Suhu Fermentasi Acetobacter Xylinum menggunakan Sensor DS18B20 - Harianingsih Harianingsih; Suwardiyono Suwardiyono; Nugroho Eko B; Rony Wijanarko (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2018)
Detection system temperature needed in the process of fermentation Acetobacter xylinum. Many food products produced from of fermentation this bacteria. Acetobacter xylinum need temperature fermentation between 28oC-32oCto growing good. To able for controlling temperature on fermentation Acetobacter xylinum, made a temperature design controller using Arduino Uno microcontroller and gauges the temperature of DS18B20 sensors. Election DS18B20 sensors because it had higher at 0,5 oC accuracy. The research covered structural testing component, testing functional and validation component. Data is the decimal form of signals delivered by a temperature on Arduino Uno microcontroller as the brain and processors. From test validation obtained prosesntase error for resistance (R) DS18B20 sensors for temperature 0oC-100oC of 0,96%. The testing Resistance (R) DS18B20 sensors for temperature 25oC-35oC of 1,12%. The measurement of temperature 25oC-35oC before calibration have prosentase error 9,65% and after calibration 0,70%. The prosentase error is still in a normal limits instrument temperature controller, so this instrument can be used as a control in the process of fermentation acetobacter xylinum.